1998
DOI: 10.1021/ja973553r
|View full text |Cite
|
Sign up to set email alerts
|

A New Family of Highly Emissive Soluble Poly(p-phenylene vinylene) Derivatives. A Step toward Fully Conjugated Blue-Emitting Poly(p-phenylene vinylenes)

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
131
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(135 citation statements)
references
References 17 publications
4
131
0
Order By: Relevance
“…Hsieh et al, for example, found out that the presence of monofunctional benzyl halogenides retards or even completely prevents gelation of the reaction mixtures and lowers the PPV's degrees of polymerization systematically. [123][124][125] He interpreted his results as support of anionic chain growth. Also Neef and Ferraris [126] and Yin and Zang [127] understood decreasing PPV molar masses and multimodal molar mass distributions obtained in the presence of 4-methoxyphenol and poly(ethylene glycol), respectively, as a consequence of anionic chain growth.…”
Section: The Gilch Routementioning
confidence: 99%
See 2 more Smart Citations
“…Hsieh et al, for example, found out that the presence of monofunctional benzyl halogenides retards or even completely prevents gelation of the reaction mixtures and lowers the PPV's degrees of polymerization systematically. [123][124][125] He interpreted his results as support of anionic chain growth. Also Neef and Ferraris [126] and Yin and Zang [127] understood decreasing PPV molar masses and multimodal molar mass distributions obtained in the presence of 4-methoxyphenol and poly(ethylene glycol), respectively, as a consequence of anionic chain growth.…”
Section: The Gilch Routementioning
confidence: 99%
“…This protonation leads to very rapid and practically irreversible deactivation of the corresponding anions, and, through regenerating the base KO t Bu, effectively preventing the anionic mode of polymerization in the presence of protic species. Nevertheless, there is a further argument emphasized in the literature that might support anionic chain growth, i.e., the effect of monofunctional benzylhalogenides 19 when additionally present in Gilch reaction mixtures: [123][124][125] species such as 19a have been reported to lower the PPVs' molar masses systematically, and to suppress gel formation. Therefore, it was an issue to rationalize the reported effects in the light of the above conclusions.…”
Section: The Anionic Chain-growth Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the absorption and emission spectra of PPV polymers 10 and 11 appear to be markedly blueshifted in comparison with those of PPDFV (λ max abs = 390 nm, λ max em = 580 nm) and DMOS-PPDFV (λ max abs = 385 nm, λ max em = 485 nm), which are the only other reported PPVs with fluorinated vinylene units. [6] To the best of our knowledge, polymer 11 shows the most blueshifted photoluminescence emission in the solid state reported to date for poly(p-phenylenevinylene)s. [20] Further photophysical and theoretical investigations are in progress in order to ascertain the role of the fluorine atoms in the emission properties of these materials and in the supramolecular organization in their solid state. [a] (sol.)…”
Section: Resultsmentioning
confidence: 99%
“…For instance, different alkyl side chains from pentyl to decyl groups were incorporated. 20 The resulting polymers show characteristic nematic texture under cross polarization at different temperature, depending on the varieties of the side group. A general route to the notable DP-PPV derivatives is depicted in Scheme 3.…”
Section: Lc Poly(p-phenylenevinylene)mentioning
confidence: 99%